Histamine and Delirium: Current Opinion - Chazot, Paul L.; Johnston, Laura; Mcauley, Edel; Bonner, Stephen (Frontiers in Pharmacology, 2019)
Delirium is a very common, but refractory clinical state, notably present in intensive care and in the growing aging community. It is characterized by fluctuating disturbances in a number of key behavioral features, namely cognition, mood, attention, arousal, and self-awareness. Histamine is arguably the most pleotropic neurotransmitter in the human brain, and this review provides a rationale, and proposes that this neuroactive amine plays a role in modulating the characteristic features of delirium. While centrally permeable H1 and H2 histamine receptor antagonists have pro-delirium potential, we propose that centrally permeable H3 histamine receptor antagonists may provide an exciting new strategy to combat delirium. The Histamine H4 receptor may also have an indirect inflammatory neuroglial role which requires further exploration.